2011
DOI: 10.1063/1.3559773
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the electrical conductivity of Pt-containing granular metals by postgrowth electron irradiation

Abstract: We have fabricated Pt-containing granular metals by focused electron beam induced deposition from the (CH3)3CH3C5H4Pt precursor gas. The granular metals are made of platinum nanocrystallites embedded in a carbonaceous matrix. We have exposed the asgrown nanocomposites to low energy electron beam irradiation and we have measured the Finally, by means of AFM measurements we observe a reduction of the volume of the samples with increasing irradiation time which we attribute to the removal of carbon molecules.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
171
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(188 citation statements)
references
References 41 publications
15
171
1
1
Order By: Relevance
“…In a series of recent papers we have started to investigate the effects of electron beam irradiation on the microstructure of FEBID samples [19]. For example, it was shown that during electron-beam irradiation the carbon-like matrix of Pt-C nanocomposites tends to graphitize, while the intergrain distance of the P t nanograins is reduced, which is due to carbon removal and to an increase of the diameter of the grains [30]. Furthermore, it was shown that electron-beam irradiation induces a roomtemperature transformation from an amorphous phase into a crystalline one for CoP t nanostructures [16].…”
Section: Discussionmentioning
confidence: 99%
“…In a series of recent papers we have started to investigate the effects of electron beam irradiation on the microstructure of FEBID samples [19]. For example, it was shown that during electron-beam irradiation the carbon-like matrix of Pt-C nanocomposites tends to graphitize, while the intergrain distance of the P t nanograins is reduced, which is due to carbon removal and to an increase of the diameter of the grains [30]. Furthermore, it was shown that electron-beam irradiation induces a roomtemperature transformation from an amorphous phase into a crystalline one for CoP t nanostructures [16].…”
Section: Discussionmentioning
confidence: 99%
“…of a percolating path between the metallic nano-particles offers the possibility to precisely tune this system from the insulating regime across the metal-insulator transition (MIT) towards metallic conductance. [17,18,19]. However, residual carbon in the deposit after the post-treatment process leads to a maximum achievable value for the electrical conductivity which is two orders of magnitude lower as compared to bulk platinum.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Porrati et al showed that the height of EBID Pt structures was reduced by ~50% after electron beam irradiation for 40 min. 20 Similarly, heating EBID a-C structures deposited on Au thin films to 450 o C results in height variations of up to 75%. 14 As concerns the Raman analysis of the electrodes, Figures 3c and 3d show the spectral window of interest for the D and G bands in the pre-and postannealed states, respectively.…”
Section: Ebid Devicesmentioning
confidence: 99%